O conceito de infância e o papel do educador em Rousseau - Queiróz, Fernanda Pinheiro de (2010)
This research investigates the concept of childhood in Jean Jacques Rousseau, and the place he made in his pedagogical project of a natural education, as well as possible contributions on the role of the teacher in this perspective. Rousseau believed that childhood was indispensable for the constitution of human being, especially considering it the beginning of any type of training. He became known as the "inventor of the modern concept of childhood," since, although not relying on science itself, anticipated, although intuitively, based on unsystematic observations, the important idea that children must be studied and perceived it same and not only referrals from the adult world. Search, therefore, this study was to understand how the author characterizes the childhood and the possible educational consequences from such a characterization. Thus, based on the goals of this research, the first chapter reconstructs the critique of Rousseau the traditional way of conceiving a child in his time. In the second chapter explains the concept of childhood Rousseau, starting from some basic principles of his theory, namely: the child must be seen and respected in their own world, strengthening the body and refinement of the senses as essential for the healthy development of children, their education by nature to guarantee the preservation of the characteristics of childhood, that is, joy, ingenuity, spontaneity, simplicity and natural goodness present in children. Finally, the third chapter, it is the adult role as driver of the development of children, pointing range and limits of making teaching from a reading of the figure of the educator of children in Rousseau